2010
DOI: 10.1103/physrevc.82.034909
|View full text |Cite
|
Sign up to set email alerts
|

Parton energy loss in heavy-ion collisions via direct-photon and charged-particle azimuthal correlations

Abstract: Charged-particle spectra associated with direct photon (γ dir ) and π 0 are measured in p + p and Au + Au collisions at center-of-mass energy √ s NN = 200 GeV with the STAR detector at the Relativistic Heavy Ion Collider. A shower-shape analysis is used to partially discriminate between γ dir and π 0 . Assuming no associated charged particles in the γ dir direction (near side) and small contribution from fragmentation photons (γ frag ), the associated charged-particle yields opposite to γ dir (away side) are e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…It generates events to be composed of primordial pions and ρ-decay pions. Their input p T distributions and v 2 (p T ) are obtained from data measurements [36][37][38][39][40][41][42][43][44][45][46]. For simplicity, we use the input harmonic plane Ψ 2 (as well as Ψ 3 discussed in Sec.…”
Section: Toy-model Simulation Of Resonance Backgroundsmentioning
confidence: 99%
“…It generates events to be composed of primordial pions and ρ-decay pions. Their input p T distributions and v 2 (p T ) are obtained from data measurements [36][37][38][39][40][41][42][43][44][45][46]. For simplicity, we use the input harmonic plane Ψ 2 (as well as Ψ 3 discussed in Sec.…”
Section: Toy-model Simulation Of Resonance Backgroundsmentioning
confidence: 99%
“…From these considerations, it can be deduced that any parton-medium interaction model which is tuned to describe single hadron suppression for a given choice of a medium model should also describe the high-z T region of the γ -h data [107,108] in the same medium model because the integrals over geometry and energy-loss probability involved are just the same. This is indeed found for the Zhang-Owens-Wang-Wang (ZOWW) model [109], for the AMY model [110], for the ASW model, and for the shower code YaJEM [111].…”
Section: γ -Hadron Correlationsmentioning
confidence: 99%
“…It originates from the energy loss experienced by the hard partonic jets initially produced from early scatterings as they traverse and interact with the highly excited nuclear matter created in these energetic collisions. The picture of parton energy loss and jet quenching has been confirmed by a wealth of experimental results observed at the Relativistic Heavy-Ion Collider (RHIC) and the Large Hadron Collider (LHC), such as the suppression of large transverse momentum hadron production [3][4][5][6][7], and the strong modification of dihadron and photon-hadron transverse momenta and azimuthal angle correlations [8][9][10][11], in central nucleus-nucleus collisions as compared to elementary nucleon-nucleon collisions. Various theoretical and phenomenological models have been developed to explain these jet modification phenomena [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], and the comparisons of theories to experimental data have shown that jet energy loss is due to the combined effects of elastic and inelastic interactions between the propagating hard partons and the constituents of the hot and dense QGP matter.…”
Section: Introductionmentioning
confidence: 82%